Cardiac Specific Knockout of p53 Decreases ER Stress-Induced Mitochondrial Damage - Chen, Qun; Thompson, Jeremy; Hu, Ying; Das, Anindita; Lesnefsky, Edward J. (Frontiers in Cardiovascular Medicine, 2019)
Endoplasmic reticulum (ER) stress contributes to cardiovascular disease including heart failure. The ER stress impairs mitochondrial respiratory chain activity and increases cell injury. p53 is a tumor suppressor protein that regulates apoptosis. Knockout (KO) of p53 leads to decreased injury in hearts following ischemia-reperfusion. We asked if KO of p53 can decrease cell injury and protect mitochondria during the induction of ER stress. Floxed p53 mice were crossed with mice carrying an α-myosin heavy chain cre to generate cardiac specific p53 KO mice. Thapsigargin (THAP) was used to induce ER stress in vivo in wild type (WT) and p53 KO mice. Mice were euthanized after 48 hours THAP treatment. TUNEL staining was used to assess myocyte death. Cardiac mitochondria were isolated for functional measurement. In WT mice, THAP treatment markedly increased cell death compared to vehicle treated hearts. In contrast, cell injury was decreased in THAP-treated p53 KO mice compared to corresponding wild type. In WT mice, THAP treatment decreased the rate of oxidative phosphorylation using pyruvate + malate as complex I substrates compared to vehicle-treated control. Complex I activity was also decreased in the THAP-treated WT mice. The rate of oxidative phosphorylation and complex I activity were not altered in THAP-treated p53 KO mice. The content of pyruvate dehydrogenase (PDH) α1 subunit was decreased in THAP-treated WT mice but not in p53 KO mice. ER stress led to a release of cytochrome c and AIF (apoptosis inducing factor) from mitochondria into cytosol in WT but not in KO mice. Knockout of p53 also preserved bcl-2 content in THAP-treated mice. Thus, KO of p53 decreased cell injury by protecting mitochondria during the ER stress.